2019
DOI: 10.1016/j.redox.2019.101280
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing redox-sensitive GFP fusions to detect in vivo redox changes in a genetically engineered prokaryote

Abstract: Understanding the in vivo redox biology of cells is a complex albeit important biological problem. Studying redox processes within living cells without physical disruption or chemical modifications is essential in determining the native redox states of cells. In this study, the previously characterized reduction-oxidation sensitive green fluorescent protein (roGFP2) was used to elucidate the redox changes of the genetically engineered Escherichia coli strain, SHuffle. SHuffle cells were demonstrated to be unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…The redox-sensitive GFP2 (roGFP2) encoded by pQE60-Grx1-roGFP2 construct, having two redox-sensitive cysteine residues at 147 th and 204 th positions, (which form disulfide bond upon oxidation) can absorb at two wavelengths 405 nm and 488 nm depending upon its oxidized and reduced state respectively. It has a fixed emission at 510 nm (Hans Reuter et al, 2019). The glutaredoxin protein (Grx1) fused to the redox-sensitive GFP2 can reversibly transfer electrons between the cellular (GSH/GSSG) pool and the thiol groups of roGFP2 at a much faster rate.…”
Section: Inhibitionmentioning
confidence: 99%
“…The redox-sensitive GFP2 (roGFP2) encoded by pQE60-Grx1-roGFP2 construct, having two redox-sensitive cysteine residues at 147 th and 204 th positions, (which form disulfide bond upon oxidation) can absorb at two wavelengths 405 nm and 488 nm depending upon its oxidized and reduced state respectively. It has a fixed emission at 510 nm (Hans Reuter et al, 2019). The glutaredoxin protein (Grx1) fused to the redox-sensitive GFP2 can reversibly transfer electrons between the cellular (GSH/GSSG) pool and the thiol groups of roGFP2 at a much faster rate.…”
Section: Inhibitionmentioning
confidence: 99%
“…Even though elevated levels of H 2 O 2 were confirmed in the cytoplasm of SHuffle (Reuter et al 2019 ), the exact concentration of this transient and highly reactive oxidant is not known. It may therefore be possible that the levels of H 2 O 2 are not sufficient and increasing the availability of H 2 O 2 can improve GPx7 driven disulfide bond formation.…”
Section: Discussionmentioning
confidence: 99%
“…To further enhance the fidelity of disulfide bond formation, a chromosomal copy of cytoplasmic DsbC (cDsbC) was inserted, resulting in the final ΔtrxB, Δgor, ΔahpC* + cDsbC strain, named SHuffle (Lobstein et al 2012). The lack of peroxidase activity of AhpC* induces oxidative stress (Reuter et al 2019), presumably due to the increased amounts of H 2 O 2 (Fig. 1).…”
Section: Engineered Redox Pathway Of Shufflementioning
confidence: 99%
See 1 more Smart Citation
“…In SHuffle cells, the periplasmic isomerase DsbC was cytoplasmically expressed to facilitate the correct folding of target proteins although efficient folding of a range of proteins depended on strain backgrounds, expression parameters and helper proteins [ 175 ]. Using redox-sensitive probes and transcriptional analysis, it was shown that SHuffle cells experienced hydrogen-peroxide stress presumably because their thioredoxin and glutathione pathways had been disrupted which impacted recombinant protein expression [ 178 ]. This problem was ingeniously solved by coupling human protein disulfide isomerase to the thiol peroxidase GPx7, creating a redox cascade in which oxidizing equivalents were transmitted from hydrogen peroxide to target proteins ( Figure 3 ).…”
Section: Areas Of Application For Thiol-based Components and Systems In Synthetic Biologymentioning
confidence: 99%